2018
DOI: 10.5382/econgeo.2018.4582
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Exhumation at the Giant Pulang Porphyry Cu-Au Deposit Using U-Pb-He Dating

Abstract: The Triassic Pulang porphyry Cu-Au deposit, located in the South Yidun terrane, is the oldest and one of the largest porphyry deposits in the southeastern Tibetan Plateau. The mineralization occurs mostly in the potassic alteration zone of the Pulang intrusive complex. U-Pb-He triple dating, namely apatite (U-Th)/He, zircon U-Pb, and zircon (U-Th)/He dating, together with inverse thermal modeling, reveals that the Pulang complex was emplaced at a paleodepth of ~5.0 to 6.5 km at 215 ± 2 Ma. The deep-level empla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…A Cretaceous regional uplift of the Eastern Tibetan Plateau is recorded by Cretaceous apatite fission track and zircon (U‐Th)/He ages of the Triassic intrusions in the Qiangtang, Yidun, and Songpan‐Ganzi Terranes (Figures and ; e.g., Lai et al, ; Wilson & Fowler, ; Tian et al, ; Zhao et al, ; Leng et al, ). This regional uplift and a suite of Cretaceous A‐type and adakite‐like intrusions (105–75 Ma) along the north‐south striking Yidun Arc (Figure ) are variously interpreted to have resulted from collision of the Yidun and Songpan‐Ganzi Terranes (Hou et al, ), subduction of the Neo‐Tethys oceanic crust (Reid et al, ), and strike‐slip pull‐apart extension in a late collisional or postcollisional environment related to the Lhasa‐Qiangtang collision (Wang et al, ; Wang, Hu, et al, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A Cretaceous regional uplift of the Eastern Tibetan Plateau is recorded by Cretaceous apatite fission track and zircon (U‐Th)/He ages of the Triassic intrusions in the Qiangtang, Yidun, and Songpan‐Ganzi Terranes (Figures and ; e.g., Lai et al, ; Wilson & Fowler, ; Tian et al, ; Zhao et al, ; Leng et al, ). This regional uplift and a suite of Cretaceous A‐type and adakite‐like intrusions (105–75 Ma) along the north‐south striking Yidun Arc (Figure ) are variously interpreted to have resulted from collision of the Yidun and Songpan‐Ganzi Terranes (Hou et al, ), subduction of the Neo‐Tethys oceanic crust (Reid et al, ), and strike‐slip pull‐apart extension in a late collisional or postcollisional environment related to the Lhasa‐Qiangtang collision (Wang et al, ; Wang, Hu, et al, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Tables S3 and S4, the ZHe and AHe ages at Zhunuo display large variations. Previous studies have shown that many factors including grain size, radiation damage, presence of U-and Th-bearing minerals or inclusions within zircon and apatite, and cooling rate can influence ZHe and AHe ages (Reiners and Farley 2001;Reiners 2005;Fitzgerald et al 2006;Shuster et al 2006;Spiegel et al 2009;Zhao et al 2015;Leng et al 2018). There is no positive correlation between equivalent spherical radius (R e q ) and (U-Th)/He ages at Zhunuo (Fig.…”
Section: Cooling and Erosion Historymentioning
confidence: 90%
“…Understanding the duration of magmatic-hydrothermal processes in porphyry deposits is fundamental for investigating porphyry deposit formation (McInnes et al 2005;Chiaradia et al 2009Chiaradia et al , 2013Sillitoe, 2010;Lang et al 2013;Buret et al 2016). Many radiometric methods (U-P b , R e -O s , 4 0 A r / 3 9 A r ) a n d l o w -t e m p e r a t u r e thermochronometry methods ((U-Th)/He) provide powerful tools for evaluating the age of mineralizing events and exhumation history of a porphyry system (Wolf et al 1996;Farley et al 1998;McInnes et al 1999;Chiaradia et al 2013;Zhao et al 2016;Leng et al 2018). Recently, precise geochronology studies indicate that porphyry deposits may form within tens of thousands of years (Pollard et al 2005;von Quadt et al 2011;Chiaradia et al 2013;Mercer et al 2015;Buret et al 2016;Tapster et al 2016;Chelle-Michou et al 2017;Li et al 2017) or several million years (Ballard et al 2001;Selby and Creaser 2001;Maksaev et al 2004;Harris et al 2008;Sillitoe and Mortensen 2010;Barra et al 2013;Lang et al 2013;Leng et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Zhongdian Cu-polymetallic area, situated in the southern segment of the Yidun arc (Figure 1a,b), is commonly regarded as one of the most fertile regions for porphyry and skarn copper deposits in China [1][2][3]. Many of the porphyry copper deposits in the Zhongdian area ( Figure 1c), such as Pulang (803.85 Mt with 0.52% Cu, 0.18 g/t Au, [4,5]), Xuejiping (54.15 Mt with 0.53% Cu, 0.06 g/t Au), Langdu (1.67 Mt with 6% Cu), Chundu, and Lannitang (36 Mt with 0.50% Cu, 0.45 g/t Au) deposits were formed in the Late Triassic as a result of westward subduction of the Garzê-Litang oceanic crust [4,5]. Recently, the recognition of some Late Cretaceous porphyry-skarn deposits, represented by the Hongshan Cu-Mo, Tongchanggou Mo-Cu, Xiuwacu W-Mo, and Relin W-Mo deposits, has drawn much attention on the collision-related metallogeny of the Zhongdian area [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%